Kontraversi Sejarah, Adat dan Moralitas di Minangkabau dalam Novel “Ketika Merah Putih Terkoyak” Karya Carl Chairun Dan Implikasinya terhadap Pembelajaran Bahasa dan Sastra - Suci Dwinitia; Afrini Rahmi (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2017)
This research is motivated by a cultural shift that is influenced by cultural development due to globalization.novel as one of the representations of society culture can be a benchmark in seeing the culture shift. The novel